2012
DOI: 10.1111/j.1476-5381.2012.02140.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine directly inhibits adipocyte differentiation through activation of the ERK 1/2 pathway

Abstract: BACKGROUND AND PURPOSECarbamazepine (CBZ), known for its anti-epileptic, analgesic and mood-stabilizing properties, is also known to induce weight gain but the pathophysiology of this adverse effect is still largely unknown. We tested the hypothesis that CBZ could have a direct effect on adipocyte development and metabolism. EXPERIMENTAL RESEARCHWe studied the effects of CBZ on morphological biochemical and molecular markers of adipogenesis, using several pre-adipocyte murine cell lines (3T3-L1, 3T3-F442A and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
1
6
0
1
Order By: Relevance
“…In our current study, we observed that Chemerin induces higher protein expressions of HSL, LPL and PPARα through the ERK1/2 signaling pathway in mature adipocyte metabolism. The result is similar to the role of Carbamazepine in 3T3‐L1 cells . PPARγ and C/EBPα are particularly important in the regulation of adipogenesis, and are highly expressed in mature adipocytes .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In our current study, we observed that Chemerin induces higher protein expressions of HSL, LPL and PPARα through the ERK1/2 signaling pathway in mature adipocyte metabolism. The result is similar to the role of Carbamazepine in 3T3‐L1 cells . PPARγ and C/EBPα are particularly important in the regulation of adipogenesis, and are highly expressed in mature adipocytes .…”
Section: Discussionsupporting
confidence: 79%
“…The result is similar to the role of Carbamazepine in 3T3-L1 cells. 29 PPARγ and C/ EBPα are particularly important in the regulation of adipogenesis, and are highly expressed in mature adipocytes. 30 Here, we observed that Chemerin induces higher expression of the lipolytic-related critical factors HSL, leptin, and LPL, and down-regulate lipogenic-related genes PPARγ and C/EBPα in mature adipocyte metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we previously reported that the role of PPARγ receptors in the antinociceptive effects of some drugs [17,18]. On the other hand, Turpin et al (2013) indicated that carbamazepine may alter cell metabolism through PPARγ receptors in mice cells [19].…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the expression levels of adipogenic genes (such as SREBP ) , genes related to lipid synthesis (such as FASN , SCD1 , MGAT1 , and DGAT1 ) , and adipokine genes (including Adipoq , leptin , and FABP4 ) were increased after carbamazepine treatment. In contrast, Turpin et al [42] have reported that carbamazepine treatment at a concentration of 500 μM inhibits adipocyte differentiation and suppresses the expression levels of adipogenic transcription factors (such as PPARγ , C/EBPα , and C/EBPβ ) and lipogenic enzymes (such as ACC , and FASN ) in 3T3-L1, 3T3-F442A, and T37i cells. However, the concentration of carbamazepine used in their study was very high (500 μM).…”
Section: Discussionmentioning
confidence: 97%